Draft Second Five Year Plan (1956-1957 to 1960-61) Part II (Vol. II - Phasing of Expenditure) - Planning Commission (Planning Commission, 1955)
Draft Second Five Year Plan (1956-1957 to 1960-61) Government of Jammu and Kashmir Development Head Irrigation Flood Control and Protection Works Miscellaneous Strengthening existing Agricultural research Weed, control Schemes Seed certification scheme Agricultural information, Audio Visual service, Basic Agricultural Covering scheme.
Jammu and Kashmir State
Jammu and Kashmir State
Keywords: Irrigation and Power; Animal Husbandry & Education; Co-operatives; Medical and Water Supply; Industrial Development; Silk Spinning; Local Bodies; Woolion Mills; Forest Industries; Drug Research; Laboratory & Tehsil; Tourism Plans; Road & Statistical